2013
DOI: 10.1371/journal.pone.0066860
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Antiretroviral Therapy and Its Effect on Survival of HIV-Infected Individuals in Jharkhand, India

Abstract: IntroductionResearch in India has extensively examined the factors associated with non-adherence to antiretroviral therapy (ART) with limited focus on examining the relationship between adherence to ART regimen and survival status of HIV infected patients. This study examines the effect of optimal adherence to ART on survival status of HIV infected patients attending ART centers in Jharkhand, India.Materials and MethodsData from a cohort of 239 HIV infected individuals who were initiated ART in 2007 were compi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 31 publications
5
58
4
1
Order By: Relevance
“…The overall adherence level in this study was 76.24%, which was a bit disparity with previous studies 75% 15 and 85% 16 conducted in Yangon Region. In fact the level of adherence in this study was rather higher than other studies across the South East Asia Region where ART adherence varied widely from 57% to 75% [19][20][21] and the study undertaken in developed country like Latin America, reported the ART adherence as 55%. 22 This may be due to the differences in timing of the study, different measuring tools to assess the adherence level, different settings, and nature of availability of the drugs.…”
Section: Discussioncontrasting
confidence: 71%
“…The overall adherence level in this study was 76.24%, which was a bit disparity with previous studies 75% 15 and 85% 16 conducted in Yangon Region. In fact the level of adherence in this study was rather higher than other studies across the South East Asia Region where ART adherence varied widely from 57% to 75% [19][20][21] and the study undertaken in developed country like Latin America, reported the ART adherence as 55%. 22 This may be due to the differences in timing of the study, different measuring tools to assess the adherence level, different settings, and nature of availability of the drugs.…”
Section: Discussioncontrasting
confidence: 71%
“…Patients with CD4 cell <200 cells/mm 3 have 3.31 times more hazard to die than patient who had CD4 cell more than 200 cells/mm 3 . The mortality is inversely proportional to CD4 count, cumulative probability of AIDS and death increased substantially with decreasing CD4 cell count Ghate et al (2011;ATCC, 2009;May et al, 2007;Rai et al, 2013;Rajasekaran et al, 2009;Kee et al, 2009). It emphasizes the importance of creating awareness about early diagnosis so that the eligible patients can be initiated on ART earlier.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies which describes the estimation of survival of HIV populations and underlying covariates effect on hazard of death among HIV patients on ART by using Cox proportional hazard model for right censored data in India and resource limited setting countries (Ghate et al, 2011;Rai et al, 2013;Kee et al, 2009;Jerene et al, 2006). However, no one has tried to identify the significant predictor associated with the survival of HIV/AIDS patients undergoing ART using parametric AFT Model under interval censored set up.…”
Section: Introductionmentioning
confidence: 99%
“…In India, adherence has been variably associated with socio-demographic characteristics (Cauldbeck et al, 2009; Rai et al, 2013; Safren et al, 2005; Sarna et al, 2008), but more consistently with psychosocial factors. Social support has been associated with higher adherence (Nyamathi et al, 2012; Shah et al, 2007), and depression is linked with poorer adherence (Anuradha et al, 2013; Nyamathi et al, 2012; Sarna et al, 2008).…”
Section: Introductionmentioning
confidence: 99%